Impacts of type of fallow and invasion by Chromolaena odorata on weed communities in crop fields in Cameroon - Ngobo, M.; McDonald, M.; Weise, Stephan F. (2004)
In the humid forest regions of southern Cameroon in central Africa, sectoral and macroeconomic policy reforms introduced in the late 1980s have led to intensified land use, which in turn has resulted in, among other environmental consequences, shortened fallow systems dominated by the Asteraceae shrub, Chromolaena odorata (L.) King and Robinson, rather than by secondary forest species. A trial was established to determine the effect of shortened fallow duration and invasion by C. odorata on the weed flora in subsequent mixed food cropping systems. Plots were established in cleared 5- to 7-year-old fallow fields in which the vegetation was either dominated by C. odorata or not, and in which the dominant fallow vegetation in the previous crop–fallow rotation had been either C. odorata, forest, or herbaceous (not dominated by C. odorata). Cassava (Manihot esculenta Crantz), maize (Zea mays L.), and groundnuts (Arachis hypogaea L.) were intercropped and weed species were assessed 6, 14, and 30 weeks after crop planting. Soil analyses were conducted to assess the influence of edaphic traits on the distribution and abundance of dominant weed species. The results clearly indicated an enrichment of the weed flora with time after planting, but little difference between fallow histories. Two groups of weed species corresponded with soil characteristics: C. odorata, Cyathula prostrata, Mariscus alternifolius, Mikania cordata, Musanga cecropioides, and Trema orientalis were preponderant on soils with high clay, N, and C contents, and Ageratum conyzoides, Cyperus sp., Haumania danckelmaniana, Paspalum conjugatum, Pouzolzia guineensis, Richardia brasiliensis, Sida rhombifolia, Stachytarpheta cayennensis, Talinum triangulare, and Triumfetta cordifolia were preponderant on sandier soils with high pH, P, and Mg contents.